AK112, a novel PD-1/VEGF bispecific antibody, in combination with chemotherapy in patients with advanced non-small cell lung cancer (NSCLC): an open-label, multicenter, phase II trialResearch in context - Yuanyuan Zhao; Gang Chen; Jianhua Chen; Li Zhuang; Yingying Du; Qitao Yu; Wu Zhuang; Yanqiu Zhao; Ming Zhou; Weidong Zhang; Yu Zhang; Yixin Wan; et al. (EClinicalMedicine, 2023)
Summary: Background: Inhibiting vascular endothelial growth factor (VEGF) function can improve the efficacy of immunotherapy by modulating the tumor immune microenvironment. AK112 is the first-in-class humanized IgG1 bispecific antibody targeting programmed death-1 (PD-1) and VEGF. This study aimed to evaluate the efficacy and safety of AK112 combined with chemotherapy in patients with advanced non-small cell lung cancer (NSCLC). Methods: This open-label, multicenter, phase II clinical trial was conducted in 11 hospitals in China. Eligible participants were adults aged 18–75 years with locally advanced or metastatic NSCLC, an Eastern Cooperative Oncology Group performance status of 0 or 1, at least one measurable lesion, and an estimated life expectancy of at least 3 months. The participants were categorized into three cohorts based on prior therapy and functional genomic alterations. Patients in cohort 1 were previously untreated advanced NSCLC, had no epidermal growth factor receptor (EGFR) or anaplastic lymphoma kinase (ALK) gene modifications, and received AK112 combined with pemetrexed (500 mg/m2) for non-squamous (non-sq)-NSCLC or paclitaxel (175 mg/m2) for sq-NSCLC plus carboplatin (area under the curve of 5 mg/mL per min) for four cycles, followed by AK112 with pemetrexed for non-sq-NSCLC and AK112 alone for sq-NSCLC as maintenance therapy. The participants in cohort 2 had advanced NSCLC with EGFR-sensitive mutations, failed previous EGFR-tyrosine kinase inhibitor (TKI) therapy, and received pemetrexed plus AK112 and carboplatin for four cycles, followed by pemetrexed plus AK112 as maintenance therapy. The participants in cohort 3 had advanced NSCLC who failed systemic platinum-based chemotherapy and anti-PD-1/programmed death-ligand 1 (PD-L1) treatments and received AK112 plus docetaxel (75 mg/m2). Two dosages of AK112 (10 or 20 mg/kg) were examined in each cohort, and the drug was administered intravenously on day 1 of each 3-week treatment cycle. The primary endpoints were the investigator-assessed objective response rate (ORR) and safety. This study was registered with ClinicalTrials.gov (NCT04736823). Findings: Eighty-three patients were enrolled from February 2021 to August 2022 and received the study treatment. Cohorts 1, 2, and 3 had 44, 19, and 20 patients, respectively. The confirmed ORR was 53.5% (23/43) [95% CI, 36.9–67.1], 68.4% (13/19) [95% CI, 43.4–87.4], and 40.0% (8/20) [95% CI, 19.1–63.9] in cohorts 1, 2, and 3, respectively. In cohort 1, the median PFS was not reached, and the 12-month PFS rate was 59.1%. In cohorts 2 and 3, the median PFS were 8.5 [95% CI, 5.5-NE] and 7.5 [95% CI, 2.3-NE] months, and the 12-month PFS rates were 35.5% and 44.5%, respectively. The most common grade ≥3 treatment-related adverse events were decreased white blood cell count [7 (8.4%)], neutropenia [5 (6.0%)], thrombocytopenia [2 (2.4%)], anemia [4 (4.8%)], and myelosuppression [2 (2.4%)]. Interpretation: AK112 plus platinum-doublet showed promising antitumor activity and safety not only in first-line treatment of advanced NSCLC patients without driver mutation but also in patients with EGFR-functional mutation who failed previous EGFR-TKI therapy and advanced NSCLC patients who failed prior systemic platinum-based chemotherapy and PD-1/PD-L1 inhibitor treatments, suggesting a valuable potential new treatment option for this patient population. Funding: Akeso Biopharma, Inc., Zhongshan, China, and National Natural Science Foundation of China.